The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3758/s13415-016-0405-8
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty is associated with increased selective attention and sustained stimulus processing

Abstract: Uncertainty about future threat has been found to be associated with an overestimation of threat probability and is hypothesized to elicit additional allocation of attention. We used event-related potentials to examine uncertainty-related dynamics in attentional allocation, exploiting brain potentials' high temporal resolution and sensitivity to attention. Thirty participants performed a picture-viewing task in which cues indicated the subsequent picture valence. A certain-neutral and a certain-aversive cue ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
81
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 66 publications
14
81
4
1
Order By: Relevance
“…Specifically, the P300 to the shocks and unpleasant pictures were enhanced when presented with unpredictable, relative to predictable, timing. This finding is consistent with previous investigations demonstrating that the P300 is larger for unexpected stimuli (Donchin, ) and a broader literature on the impact of unpredictability on enhanced sensory and attentional processing of aversive stimuli (Carlsson et al, ; Dieterich et al, ). Together, the startle probe and aversive stimulus ERP results suggest that unpredictability heightens motivated attention both in anticipation and during processing of threat.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, the P300 to the shocks and unpleasant pictures were enhanced when presented with unpredictable, relative to predictable, timing. This finding is consistent with previous investigations demonstrating that the P300 is larger for unexpected stimuli (Donchin, ) and a broader literature on the impact of unpredictability on enhanced sensory and attentional processing of aversive stimuli (Carlsson et al, ; Dieterich et al, ). Together, the startle probe and aversive stimulus ERP results suggest that unpredictability heightens motivated attention both in anticipation and during processing of threat.…”
Section: Discussionsupporting
confidence: 93%
“…For example, one study found that aversive pictures that were preceded by an uncertain valence cue, relative to a certain valence cue, elicited greater skin conductance response and self-reported negative mood (Grupe & Nitschke, 2011). Similarly, a recent study found that neutral and aversive pictures that were preceded by an uncertain valence cue, relative to a certain neutral or certain aversive cue, produced a greater P2 and late positive potential (LPP) response (Dieterich, Endrass, & Kathmann, 2016). To further investigate the impact of predictability on emotional reactivity to the actual aversive stimulus, the current study also measured ERP responses elicited by shocks and unpleasant pictures during the NPU-threat task.…”
Section: Nelson and Hajcak | 1181mentioning
confidence: 99%
“…Its early (<1,000 ms) and late (>1,000 ms) portions may reflect partially distinct attentional processes, that is, obligatory attentional allocation (Weinberg, & Hajcak, 2010) and deliberate elaboration (Foti, & Hajcak, 2008), respectively. Similarly, stimuli with unpredictable valence elicited enhanced P2 and N2 amplitudes (Dieterich et al, 2016;Lin et al, 2015). The early LPP increases in response to cues for threat of shock (Bublatzky, & Schupp, 2012) and during resolution of uncertainty (Dieterich, Endrass, & Kathmann, 2016), and decreases to signify uncertainty-related avoidance (Gole, Schäfer, & Schienle, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Importantly, postsensory components reportedly capture uncertainty-related modulations in attention. The early LPP increases in response to cues for threat of shock (Bublatzky, & Schupp, 2012) and during resolution of uncertainty (Dieterich, Endrass, & Kathmann, 2016), and decreases to signify uncertainty-related avoidance (Gole, Schäfer, & Schienle, 2012). Similarly, stimuli with unpredictable valence elicited enhanced P2 and N2 amplitudes (Dieterich et al, 2016;Lin et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation